ELEMENTOS DE LOS MODELOS DETERMINANTES DEL CLIMA ORGANIZACIONAL - Velázquez, Ma. Del Rosario García; Gracia, Tirso Javier Hernández; Zorrilla, Dolores Margarita Navarrete; García, Alejandra Corichi; Monjaraz, Germán Sánchez (European Scientific Journal, ESJ, 2014)
From importing the organizational climate has with in organizations, since it is the perception of human capital in relationtotheenvironment in which it is developed and share dwithco workers, is considered as a factor that reflects the facilities or obstaclesfacedby the worker to work in the employment context, for this reasonis considered extremely important and essential to have instrumentsto determine thelevel of organization alclimateperceivedby workers. There for edocumentaryre search, is ananalysis of the various existing measurement instruments in the literature regarding the organizational climate in differentareas (private companies, educational organizations, government agencies, health care organizations, and others) purpose. The importance of the analysis of the seinstruments is that they are indispensable to assessthe climate with in organization stool, there by generating strategies to directthea ctions, in orderto balance and achieve organizational behavior, group and individual positive. To measure the organizational climate has been identified in the literature to develop a largenumber of measuring instruments, amongwhichmay be mentione distheonepreparedby Mellado (2004), Chiang (2003), Brown and Leigh (1996) between other. They consider different dimensions of the work environment, such as individual responsibility, remuneration, risk and decisionmaking, support, tolerance, conflict, amongothers. The methodology consisted of literature review to identify various measurement instruments developed. Of which the definitions of organization alclimate addressed by the authors, measuring instruments, the oretical approaches, dimensions and values of validity and reliability in each were analyzed to determine if they are useful and feasible to apply to the Mexican contextd etermined by the investigat or according to the irinterests, stillarises at theend of the presentres earch findings and recommend ations for the selection and analysis instruments forme asuringorganizational climate, according to the type of organization, purposesassessment and identified organizational problems.